MicroRNAs in Oncology - Yusuf Tutar (Global Journal of Biotechnology and Biomaterial Science - Peertechz Publications, 2015)
MicroRNAs (miRNAs) are a family of short non-coding RNA molecules which contain about 18-24 nucleotides.miRNAs play significant regulatory roles in biological processes (cell proliferation, differentiation,survival and motility). miRNAs are essential regulators of coding genes at the post-transcriptional level.The biogenesis of miRNAs is composed of complex processes, and human genome contains approximately two thousand miRNAs (http://www.mirbase.org) [1,2]. Expression patterns of miRNAs have been found to have links with pathogenesis of many diseases including neurodegenerative diseases, diabetes, cardiovascular diseases,and particularly cancer.miRNAs have been identified as a critical biomarker for treatment, diagnosis, and progression of cancer.Experimental and computational data indicates that miRNAs are up-regulated or down-regulated in cancer cells, and therefore, they have oncogenic (oncomirs) or tumor-suppressive roles in apoptosis,angiogenesis, proliferation, metastasis, and differentiation in cancer cells [